2015
DOI: 10.1111/wrr.12389
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous perfusion before and during surgery in obese and nonobese patients

Abstract: Hypoxia at the surgical site impairs wound healing and oxidative killing of microbes. Surgical site infections are more common in obese patients. We hypothesized that subcutaneous oxygen tension (P sq O 2 ) would decrease substantially in both obese and non-obese patients following induction of anesthesia and after surgical incision. We performed a prospective observational study that enrolled obese and non-obese surgical patients and measured serial P sq O 2 before and during surgery. Seven morbidly obese and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was found that morbidly obese individuals had lower pO 2 levels in subcutaneous WAT (sWAT) of the upper arm as compared to lean subjects, determined the morning after surgery . However, other studies in which sWAT oxygenation has been measured both during and after surgery showed opposite results, with increased or no significant difference in WAT pO 2 between obese and lean individuals . Notably, these initial studies assessed oxygenation in WAT of the upper arm, which is not of crucial importance for whole‐body metabolism.…”
Section: Altered Adipose Tissue Oxygen Partial Pressure In Obesitymentioning
confidence: 99%
“…It was found that morbidly obese individuals had lower pO 2 levels in subcutaneous WAT (sWAT) of the upper arm as compared to lean subjects, determined the morning after surgery . However, other studies in which sWAT oxygenation has been measured both during and after surgery showed opposite results, with increased or no significant difference in WAT pO 2 between obese and lean individuals . Notably, these initial studies assessed oxygenation in WAT of the upper arm, which is not of crucial importance for whole‐body metabolism.…”
Section: Altered Adipose Tissue Oxygen Partial Pressure In Obesitymentioning
confidence: 99%
“…Studies investigating adipose tissue Po 2 in rodents report a significant decrease of O 2 availability with increased fatness as well as increased expression of hypoxia-related genes, such as hypoxia-inducible transcription factor-1 alpha (HIF-1α) (Rausch et al, 2008;Ye et al, 2007). However, results in humans are inconsistent, with studies reporting similar (Hiltebrand et al, 2008;Kaiser et al, 2016), lower (Cifarelli et al, 2020;Kabon et al, 2004;Lawler et al, 2016;Pasarica et al, 2009), and higher (Goossens et al, 2011(Goossens et al, , 2018 adipose tissue Po 2 in obese compared to lean individuals. In addition, Vink et al (2017) report a decrease in adipose tissue Po 2 after diet-induced weight loss.…”
Section: Introductionmentioning
confidence: 99%